Delivering the goods? German industrial relations institutions during the COVID‐19 crisis. Issue 2 (15th July 2022) - Behrens, Martin; Pekarek, Andreas
Abstract: The COVID‐19 pandemic has caused labor market disruptions at an unprecedented scale and is akin to a stress test for industrial relations institutions. Drawing on a large‐scale ( n = 6111) study of German employees, we empirically investigate whether and how the two institutions comprising Germany's dual system of employee representation—works councils and collective bargaining—have delivered on their protective potential and mitigated the impact of the pandemic on workers. We demonstrate that employees in representative environments fare better on a range of protective outcomes.